Spiritual and Customary Authority of Damang in Post-Divorce Child Support: Rethinking Indigenous Justice in Dayak Ngaju Communities - Puji Rahmiati; Anas Maulana (IAIN Palangka Raya, 2025)
Dayak Ngaju customary law endows the Damang (Dayak customary leader) with formal authority, both as a customary and spiritual figure. In divorce law, the enforcement of child support rulings often faces implementation challenges, potentially undermining the Damang’s socio-spiritual legitimacy. The study aimed to examine the authority of the Damang in handling child support obligations after divorce within the Dayak Ngaju community. The empirical research employed a socio-legal approach, with primary data collected and validated through triangulation techniques, and analyzed within the frameworks of customary law, positive law, and Islamic law. The findings confirm that the Damang holds formal authority to issue and supervise customary rulings. However, this structural authority has not been fully effective due to the absence of adequate enforcement mechanisms. The study proposes a hybrid legal model integrating Damang’s resolution methods with state enforcement to ensure justice and child welfare. As the spearhead of customary justice, the Damang’s role contributes to the discourse on the authority of indigenous leaders, the rights of indigenous communities, and access to justice.